EFFECT OF ONLINE SERVICE QUALITY OF MAKEUPPUCINO WEBSITE STORE TO CUSTOMER SATISFACTION - Iskandar, Safira Azaria; Fachira, Ira (Journal of Business and Management, 2017)
Abstract. Recently there are a lot of online retail in Indonesia. Makeupuccino is an online store based in Bandung that sales makeup and other cosmetics stuff. As the competition between online retails getting higher, Makeupuccino need improves their service quality to maintain their customer’s satisfaction.  This study aims to explore customers’ perception of online retail store service quality and how it effects customer satisfaction. Reliability, responsiveness, security and web-design represent the service quality. Data was collected from Makeupuccino customers. Makeupuccino’s website store has already got an excellence online service quality. Customer’s satisfaction of Makeupuccino website store is also considered as excellence. From four of the online service quality dimensions : reliability, responsiveness, security and web-design, the reliability dimension is believed as the most significant dimensions  towards customers satisfaction. Makeupuccino needs to maintain their excellence online service quality. And Makeupuccino needs to keep the trust from the customers. Trust is also important for the reliability dimensions of the online service quality. For further research, researchers recommend to increase the samples in order to have more reliable results for the population. And give adjustment on the online service quality measurement tools in order to obtain the desired results.